PENGUKURAN KINERJA PEMBANGUNAN MANUSIA DESA/KECAMATAN KABUPATEN SERAM BAGIAN BARAT DENGAN MENGGUNAKAN ANALISIS MULTIVARIAT - Amaluddin Amaluddin; Rukmuin Wilda Payapo; Abdul Aziz Laitupa (Jurusan Ekonomi Pembangunan, FEB Universitas Pattimura, 2017)
The first purpose of this paper is to develop or construct a new human development composite index and applied to measure the performance of human development in the village / district of West Seram Regency. The second, to develop the priority scale of human development planning. This paper applies quantitative analysis method that is principal component regression (PCR) and clustering analysis (CA). Data is sourced from the Regional Development Planning Agency (Bappeda) of West Seram Regency of year 2016. Application of principal component regression and clustering analysis method, aims to improve the aggregation method of human development composite index developed by UNDP. Composite index compositions resulting from principal component regression and IPM-UNDP largely result in different ranking information but in some villages have the same rank. Based on K-means clustering analysis, there were 3 main clusters, namely high, medium and low cluster. The number of villages in the high cluster is 6 villages, the medium cluster is 13 villages and low cluster is 14 villages.